Biological false‐positive venereal disease research laboratory test in cerebrospinal fluid in the diagnosis of neurosyphilis – a case‐control study. (6th December 2017) - Zheng, S.; Lin, R.J.; Chan, Y.H.; Ngan, C.C.L.
Abstract: Background: There is no clear consensus on the diagnosis of neurosyphilis. The Venereal Disease Research Laboratory (VDRL) test from cerebrospinal fluid (CSF) has traditionally been considered the gold standard for diagnosing neurosyphilis but is widely known to be insensitive. Objective: In this study, we compared the clinical and laboratory characteristics of true‐positive VDRL‐CSF cases with biological false‐positive VDRL‐CSF cases. Methods: We retrospectively identified cases of true and false‐positive VDRL‐CSF across a 3‐year period received by the Immunology and Serology Laboratory, Singapore General Hospital. A biological false‐positive VDRL‐CSF is defined as a reactive VDRL‐CSF with a non‐reactive Treponema pallidum particle agglutination (TPPA)‐CSF and/or negative Line Immuno Assay (LIA)‐CSF IgG. A true‐positive VDRL‐CSF is a reactive VDRL‐CSF with a concordant reactive TPPA‐CSF and/or positive LIA‐CSF IgG. Results: During the study period, a total of 1254 specimens underwent VDRL‐CSF examination. Amongst these, 60 specimens from 53 patients tested positive for VDRL‐CSF. Of the 53 patients, 42 (79.2%) were true‐positive cases and 11 (20.8%) were false‐positive cases. In our setting, a positive non‐treponemal serology has 97.6% sensitivity, 100% specificity, 100% positive predictive value and 91.7% negative predictive value for a true‐positive VDRL‐CSF based on our laboratory definition. HIV seropositivity was an independent predictor of a true‐positive VDRL‐CSF. Conclusion: Biological false‐positive VDRL‐CSF is common in a setting where patients are tested without first establishing a serological diagnosis of syphilis. Serological testing should be performed prior to CSF evaluation for neurosyphilis.